2016
DOI: 10.1111/bph.13571
|View full text |Cite
|
Sign up to set email alerts
|

Azoreductases in drug metabolism

Abstract: Azoreductases are flavoenzymes that have been characterised in a range of prokaryotes and eukaryotes. Bacterial azoreductases are associated with the activation of two classes of drug, azo drugs for the treatment of inflammatory bowel disease and nitrofuran antibiotics. The mechanism of reduction of azo compounds is presented that requires tautomerisation of the azo compound to a quinoneimine and provides a unifying mechanism for the reduction of azo and quinone substrates by azoreductase. The importance of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 119 publications
(137 reference statements)
1
53
0
1
Order By: Relevance
“…The quinone reduction activities of azoreductase from different microorganisms and their dependence on NAD(P)H cofactor need to be classified as NAD(P)H quinone oxidoreductases (NQOs) (Liu et al 2008(Liu et al , 2009Ryan et al 2010a, b;Hervas et al 2012). As reviewed by Ryan (2017) and Koppel et al (2017), there are very few NQOs characterized from human gut bacterial strains. Recently, Ryan et al (2014) identified the NAD(P)H quinone oxidoreductase activity in azoreductase from P. aeruginosa and demonstrated that the azoreductases and the NAD(P)H quinone oxidoreductases belong to the same FMN-dependent azoreductase superfamily.…”
Section: Azoreductase Classificationmentioning
confidence: 99%
“…The quinone reduction activities of azoreductase from different microorganisms and their dependence on NAD(P)H cofactor need to be classified as NAD(P)H quinone oxidoreductases (NQOs) (Liu et al 2008(Liu et al , 2009Ryan et al 2010a, b;Hervas et al 2012). As reviewed by Ryan (2017) and Koppel et al (2017), there are very few NQOs characterized from human gut bacterial strains. Recently, Ryan et al (2014) identified the NAD(P)H quinone oxidoreductase activity in azoreductase from P. aeruginosa and demonstrated that the azoreductases and the NAD(P)H quinone oxidoreductases belong to the same FMN-dependent azoreductase superfamily.…”
Section: Azoreductase Classificationmentioning
confidence: 99%
“…Ryan is also an author of a review (Ryan, 2017) and a co-author of the paper by Da Silva et al 2017.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…There are two classes of drug-metabolizing enzymes in bacteria discussed in this themed section: the azoreductases (Ryan, 2017) and the arylamine N-acetyltransferases (Kubiak et al, 2017). The azoreductases, which are found in gut bacteria, activate azo prodrugs, such as balsalazide, used in inflammatory bowel disease and also the nitrofuran group of antibiotics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…No fluorescencec ould be observed before the reduction reactiondue to the FRET-mediated quenching. After the enzyme treatment, the emission peak at 465 nm was observed when excited with 760 nm light, which is consistentwith the fluorescence emission of the TPE dots.As the azoreductases are reportedly over-expressedi nh ypoxic cancer cells, [38][39][40][41] we further tested whether PEG-Azo-TPE aggregates can be reducedt or estore TPE fluorescencei nh ypoxic tumor cell cultures. Figure 3s hows the fluorescence images of adherent A549 cells after the incubation with PEG-Azo-TPE under different oxygen concentrations.…”
mentioning
confidence: 99%